English as the Lingua Franca in Europe - G. A. Demin; L. A. Ulianitckaia (Дискурс, 2022)
Introduction. Throughout several decades, English has been strengthening its position as lingua franca in international communication. The relevance of the given study is justified by the examination of the English language from the perspective of contact variantology and in the context of gradually emerging new version of English – Euro-English. The aim of the presented work is to consider the socio-political prerequisites for the strengthening of the English language role for intra-European communication, as well as to try to explain the significance of Brussels for this process. Methodology and sources. Scientific publications of domestic and foreign linguists, sociolinguists (D.S. Borodina, Z.G. Proshina, B. Kachru, D. Crystal, E. Edwards), as well as interviews with European politicians and public figures (Michel Guerin, Pascal Smet, Sven Gatz) all comprise the research material. The method of synthesis and analysis, descriptive method, comparative language analysis is used in the process of work on this article. Results and discussion. The widespread usage of English in Europe has led to the creation of several mixed language variants and intra-European communication in English gives the latter the status of a supranational communication language. Belgium is seen as the center for the formation of this new language variant, which is explained by the representation of a significant number of international organizations and corporations in Brussels. In the context of the competition between French and Dutch, the difficult linguistic situation in Belgium finds a peculiar resolution in the regular use of English which some activists propose to make the third official language of the Brussels-Capital Region. Euro-English has already acquired several characteristic lexical, morphosyntactic and phonetical features, whilst the withdrawal of Great Britain from the European Union has provided serious possibilities for Euro-English to continue its formation as an independent language variant free from “care” and control of English native speakers. Conclusion. The existence of the English language variants involves the preservation of uniqueness for each nation where these are used, as well as the enrichment of the language from which these variants are derived from. Gradual formation of Euro-English confirms the presence of high number of professional and everyday communications under which the representatives of various European nations find common language – and that is English.